Study of the influence of ultra-high molecular weight polyethylene and high-density polyethylene on the properties and structure of ethylene propylene diene monomer rubber - M. D. Sokolova; A. R. Khaldeeva; M. L. Davydova; A. F. Fedorova; N. V. Shadrinov (Тонкие химические технологии)
Objectives. The study set out to examine the impact of pre-mixed ultra-high molecular weight polyethylene (UHMWPE) and high-density polyethylene (HDPE) on a range of properties and structural characteristics of SKEPT-50 ethylene propylene diene monomer (EPDM) rubber.Methods. The production of rubber mixtures involved the pre-mixing of rubber with UHMWPE and HDPE in a Brabender PL 2200-3 plasti-corder chamber (Germany) at a temperature of 160°C, for a period of 6 min, and with a rotor speed of 60 rpm. The polyethylene constituents were incorporated into the rubber compound at concentrations of 5, 10, and 15 pts. wt. The subsequent introduction of the principal constituents of the rubber mixture was conducted in an SYM laboratory mill (China) for a period of 30 min at a temperature of no more than 100°C. The vulcanization of the samples was conducted in an Y1000D vacuum hydraulic press (China) at a temperature of 185°C for a period of 35 min. The investigation of vulcanization and physical and mechanical properties was conducted in accordance with the established protocols. The analysis of the rubber supramolecular structure was conducted using a JEOL JSM-6840 LV scanning electron microscope (Japan).Results. The results demonstrate that an increase in the proportion of HDPE and UHMWPE to 15 pts. wt leads to a notable enhancement in the hardness of the rubbers by 10 and 5 Shore A units, respectively. The frost resistance coefficient at −45°C demonstrates an increase with the incorporation of 10 pts. wt of HDPE to reach a value of 0.229, and a further increase with the incorporation of 15 pts. wt of UHMWPE to reach a value of 0.260. The degree of swelling of rubbers in a DOT-4 brake fluid environment is observed to decrease to 13% for rubbers with HDPE and 19% with UHMWPE. The degree of swelling of rubbers in the DOT-4 brake fluid environment is observed to decrease to 13% for rubbers with HDPE and 19% with UHMWPE. While an increase in the HDPE content results in a 5% increase in volumetric wear, an increase in the UHMWPE content is associated with a 45% decrease in volumetric wear. The introduction of UHMWPE was observed to result in the formation of inclusions of varying shapes and sizes within a range of 50–100 µm. The transition zone between UHMWPE and rubber is characterized by a smooth surface. No evidence of cracks or micro-tears between the polymer phases, which could potentially form during low-temperature splitting, was observed. This finding indicates the presence of favorable interfacial interactions, which can be linked to the observed enhancements in resistance to aggressive liquids and abrasion, as well as the improved tensile frost resistance coefficient. The supramolecular structure of rubber samples combined with HDPE is more pronounced and exhibits greater relief than that of the original rubber. This is indicative of a more uniform distribution within the matrix volume, which can be attributed to the high fluidity of the HDPE melt.Conclusions. Rubbers modified with UHMWPE, in comparison with HDPE, exhibit enhanced resistance to wear, oil, and frost, while maintaining their elastic and strength properties. It was established that rubber containing 15 pts. wt of UHMWPE exhibits optimal properties and can thus be recommended for use in sealing rubber products.